Making Standard Operating Procedures (SOP) at Rupit Hospital, North Musi Rawas Regency - Pettanase, Ismail; Ardha, Dea Justicia; Rani, Febrina Hertika; Syamsul, Syamsul; Chandra, Muhammad Boby (Unram Journal of Community Service, 2025)
This service aims to increase understanding of the optimization of Standard Operating Procedures (SOPs) to improve the quality of health services at Rupit Hospital, North Musi Rawas Regency. This activity uses a visual presentation method to provide in-depth explanations related to SOPs, followed by a question and answer session to support direct interaction and small group discussions that encourage the exchange of understanding. In addition, supporting materials in the form of brochures or pamphlets were provided to facilitate the dissemination of information to the community. The results of the activity showed that Rupit Hospital already has a good SOP, but its application has not been specifically classified in each department. The conclusion of this activity is that optimizing SOPs through a holistic approach can be a strategic step in improving the quality of health services in hospitals